A Developed Shear Wave Source for Shallow Seismic Survey - Yordkayhun, Sawasdee; Wattanasen, Kamhaeng; Na Suwan, Jamras (Trends in Sciences, 2024)
Shear wave velocity is a fundamental parameter in determining geological structures and soil characteristics for geotechnical and earthquake engineering studies. In shallow seismic data acquisition, shear wave is generated by various seismic sources. Although the data quality is affected by the choices of the seismic source, applying highly efficient sources is sometimes limited for some users and by the budget available for a project. Therefore, this work aims to design and develop an effective shear wave seismic source as an alternative for shallow seismic surveys. The developed source consists of 4 main parts, including base plate, activated mass, lifting and shooting system, body and transportation system. It is simply operated by lifting an activated mass with a sling and puller to the armed position. Under this condition, an attached spring is under compression and the maximum potential energy is stored. When the mass is released and horizontally hit the base plate, shear wave is generated by the momentum and energy transferred from the base plate into the ground. To evaluate the source capability, a comparison of the conventional and the developed source was performed at a test site. The recorded data were compared both in qualitative and quantitative manners based on the signal-to-noise ratio, energy and frequency content, signal penetration, and repeatability. It was found that signal energy generated by one blow of the developed source is equivalent to approximately three-fold of the conventional source. There is a remarkably higher repeatability from the developed source than that from the conventional source. Moreover, it is easy to operate, portable, and minimizes required man power. Overall, the new shear source is suitable and has potential application for shallow seismic surveys. HIGHLIGHTS The new shear wave seismic source has been developed and tested as an alternative source for shallow seismic surveys The key advantages of the developed source are that it is simple to operate, reduces required manpower, fairly cost-effective, transportable, safe, and has a minimal environmental impact There is a noticeably higher input signal energy transfer offered by the source leading to the deeper target depth of investigation The better repeatable waveform led to greater accuracy of the 1st break picking in the data processing GRAPHICAL ABSTRACT